Is EEG Suitable for Marketing Research? A Systematic Review - Bazzani, Andrea; Ravaioli, Silvio; Trieste, Leopoldo; Faraguna, Ugo; Turchetti, Giuseppe (Frontiers in Neuroscience, 2020)
Background: In the past decade, marketing studies have greatly benefited from the adoption of neuroscience techniques to explore conscious and unconscious drivers of consumer behavior. Electroencephalography (EEG) is one of the most frequently applied neuroscientific techniques for marketing studies, thanks to its low cost and high temporal resolution. Objective: We present an overview of EEG applications in consumer neuroscience. The aim of this review is to facilitate future research and to highlight reliable approaches for deriving research and managerial implications. Method: We conducted a systematic review by querying five databases for the titles of articles published up to June 2020 with the terms [EEG] AND [neuromarketing] OR [consumer neuroscience]. Results: We screened 264 abstracts and analyzed 113 articles, classified based on research topics (e.g. product characteristics, pricing, advertising attention and memorization, rational and emotional messages) and characteristics of the experimental design (tasks, stimuli, participants, additional techniques). Conclusions: This review highlights the main applications of EEG to consumer neuroscience research and suggests several ways EEG technique can complement traditional experimental paradigms. Further research areas, including consumer profiling and social consumer neuroscience, have not been sufficiently explored yet and would benefit from EEG techniques to address unanswered questions.